Functional equivalency of amphioxus and vertebrate Pax258 transcription factors suggests that the activation of mid-hindbrain specific genes in vertebrates occurs via the recruitment of Pax regulatory elements - Krelová, Jana; Holland, Linda Z; Schubert, Michael; Burgtorf, Carola; Benes, Vladimír; Kozmik, Zbynek (Gene, 2002)
Pax genes encode transcription factors that control key developmental decisions in various animal phyla. The Pax2/5/8 subfamily plays a key role in specification and/or maintenance of vertebrate mid-hindbrain boundary (MHB) region by directly regulating expression of other genes, most notably En2. In the invertebrate chordate amphioxus, expression of AmphiPax2/5/8 is found in many sites that are homologous to the regions of the vertebrate embryo expressing orthologous genes Pax2, Pax5 or Pax8. However, no co-expression of AmphiPax2/5/8 and AmphiEn is detected in the region of the neural tube that might correspond to the vertebrate MHB. Based on this observation and the absence of AmphiWnt expression in this region it appears that amphioxus does not have a MHB. Here we investigated the possibility that the AmphiPax2/5/8, as a key component of MHB development, has lost some of the properties of its vertebrate counterparts. We have analyzed both the DNA-binding and transactivation properties of AmphiPax2/5/8 as well as its ability to interact with the groucho co-repressor. In all these assays AmphiPax2/5/8 is indistinguishable from the human Pax5. In addition, we found two alternatively spliced AmphiPax2/5/8 isoforms that function similarly to the alternatively spliced isoforms of human Pax8. Analysis of the AmphiEn regulatory region provided no evidence for AmphiPax2/5/8 binding and transactivation. Therefore, in amphioxus, AmphiPax2/5/8, although capable of performing all the necessary functions has not been recruited for a developmental mechanism which usually sets up MHB development in vertebrates.
Keywords: Molecular Sequence Data; Cell Line; jaderné proteiny; DNA-Binding Proteins; sekvence aminokyselin; trans-aktivátory; Protein Binding; Nuclear Proteins; DNA; alternativní sestřih; regulační oblasti nukleových kyselin; Gene Expression Regulation; PAX8 Transcription Factor; Regulatory Sequences, Nucleic Acid; reportérové geny; transkripční faktor PAX8; Promoter Regions, Genetic; Mice; Tumor Cells, Cultured; Paired Box Transcription Factors; buňky 3T3; Trans-Activators; Transcription Factors; Chordata, Nonvertebrate; regulace genové exprese; transkripční faktory; sekvence nukleotidů; Base Sequence; 3T3 Cells; obratlovci; Genes, Reporter; PAX5 Transcription Factor; zvířata; Alternative Splicing; Humans; rombencefalon; Vertebrates; Amino Acid Sequence; Rhombencephalon; Recombinant Fusion Proteins; vazba proteinů; rekombinantní fúzní proteiny; nižší strunatci; PAX2 Transcription Factor; myši; promotorové oblasti (genetika); DNA vazebné proteiny; buněčné linie; molekulární sekvence - údaje; aktivátorový protein specifický pro B-buňky; sekvenční homologie aminokyselin; nádorové buňky kultivované; transkripční faktor PAX2; lidé; Sequence Homology, Amino Acid; transkripční faktory paired box; Animals